Does intensive multimodal treatment for maternal ADHD improve the efficacy of parent training for children with ADHD? A randomized controlled multicenter trial. (30th June 2015) - Jans, Thomas; Jacob, Christian; Warnke, Andreas; Zwanzger, Ulrike; Groß‐Lesch, Silke; Matthies, Swantje; Borel, Patricia; Hennighausen, Klaus; Haack‐Dees, Barbara; Rösler, Michael; Retz, Wolfgang; von Gontard, Alexander; et al.
Abstract : Background: This is the first randomized controlled multicenter trial to evaluate the effect of two treatments of maternal attention‐deficit hyperactivity disorder (ADHD) on response to parent–child training targeting children's external psychopathology. Methods: Mother–child dyads ( n = 144; ADHD according to DSM‐IV; children: 73.5% males, mean age 9.4 years) from five specialized university outpatient units in Germany were centrally randomized to multimodal maternal ADHD treatment [group psychotherapy plus open methylphenidate medication; treatment group (TG): n = 77] or to clinical management [supportive counseling without psychotherapy or psychopharmacotherapy; control group (CG): n = 67]. After 12 weeks, the maternal ADHD treatment was supplemented by individual parent–child training for all dyads. The primary outcome was a change in the children's externalizing symptom scores (investigator blinded to the treatment assignment) from baseline to the end of the parent–child training 6 months later. Maintenance therapy continued for another 6 months. An intention‐to‐treat analysis was performed within a linear regression model, controlling for baseline and center after multiple imputations of missing values. Results: Exactly, 206 dyads were assessed for eligibility, 144 were randomized, and 143 were analyzed (TG: n = 77; CG: n = 66). After 6 months, no significant between‐group differences were found in change scores for children's externalizing symptoms (adjusted mean TG‐mean CG=1.1, 95% confidence interval −0.5–2.7; p = .1854), although maternal psychopathology improved more in the TG. Children's externalizing symptom scores improved from a mean of 14.8 at baseline to 11.4 (TG) and 10.3 (CG) after 6 months and to 10.8 (TG) and 10.1 (CG) after 1 year. No severe harms related to study treatments were found, but adverse events were more frequent in TG mothers than in CG mothers. Conclusions: The response in children's externalizing psychopathology did not differ between maternal treatment groups. However, multimodal treatment was associated with more improvement in maternal ADHD. Child and maternal treatment gains were stable (CCT‐ISRCTN73911400).